Does Capital Account Openness Lower Inflation? - Gupta, Abhijit Sen (2012)
This paper investigates the relationship between capital account openness and inflation since the 1980s. It argues that widespread capital account liberalization during the last two decades appears to have contributed to the worldwide disinflation observed during the same period. The paper builds a theoretical model to motivate the presence of a negative link between financial integration and inflation. It tests the prediction of the theoretical model by employing static and dynamic panel data procedures. Financial integration appears to discipline monetary authorities, or to help them convince the private sector that they will be more disciplined in the future.